Depletion of conventional CD4+ T cells is required for robust priming and dissemination of tumor antigen-specific CD8+ T cells in the setting of anti-CD4 therapy - Keisuke Shirai; Tiffany Chen; Mary Jo Turk; Delaney E Ramirez; Christo P C Dragnev; Tyler G Searles; Nathaniel Spicer; J Louise Lines; Aaron R Hawkes; Wilson L Davis; Asmaa Mohamed; Joseph D Phillips; et al. (Journal for ImmunoTherapy of Cancer)
Background Overcoming immune suppression is a major barrier to eliciting potent CD8+ T cell responses against cancer. Treatment with anti-CD4 monoclonal antibody is an effective means for eliminating CD4+Foxp3+ regulatory (Treg) cells in preclinical models and has also demonstrated efficacy in early clinical trials. However, the underlying basis for treatment efficacy, more specifically the implications of codepleting other CD4-expressing cell compartments in tumor-bearing hosts, is not well understood.Methods Tumor-bearing mice were treated with anti-CD4 versus other therapies that preserve helper T cell function, and the priming, tissue distribution, and maintenance of tumor antigen-specific CD8 T cells were assessed. Antibody blockade and transgenic mouse models were used to determine the mechanisms of CD8 T cell priming. Single-cell RNA-sequencing (scRNAseq) was used to further characterize CD8 T cells that are primed by anti-CD4 therapy and to identify immunosuppressive CD4 T cell subsets in human melanoma following immune checkpoint blockade (ICB).Results Comparing anti-CD4 to dual ICB therapy, we show that anti-CD4 facilitates more robust priming of TCF-1+, IL-2-producing, tumor-specific CD8+ T cells that disseminate to tissues and form memory. By decoupling priming from homeostatic proliferation and associated cytokines, we find that anti-CD4 functions independently of creating homeostatic space for CD8+ T cells. We also show that depletion of CD4-expressing antigen-presenting cell subsets is not required for anti-CD4 efficacy. Instead, robust tumor-specific CD8+ T cell priming and memory generation required the removal of total antigen-specific CD4+ T cells, including both Tregs and CD4+ Foxp3-negative conventional (Tconv) cells. In particular, the elimination of CD4+ Tconv cells was necessary for the accumulation and maturation of conventional type-1 dendritic cells in tumor-draining LNs, which were required for CD8+ T cell priming. Accordingly, anti-CD4 treatment restored CD8+ T cell responses in mice cotreated with dual ICB. scRNAseq of melanoma tumors from patients who received ICB revealed the presence of Tr1 and Treg subsets, as well as CD4+ Tconv subsets that lacked clear transcriptional evidence of helper differentiation.Conclusions These findings underscore the underappreciated benefit of depleting CD4+ Tconv cells to promote systemic primary and memory CD8+ T cell responses against cancer.